Supply chain management: leveraging reverse auctions - Prokop, Darren (Henry Stewart Talks, 2020)
How does a standard auction work, How does a reverse auction work, Financial bids vs. requests for proposals (RFPs), Collusion, Rules of auctioning, Request for Information (RFIs), Buyer’s and vendor’s information, The dangers of auctioning